Development of Competitiveness of Future Teachers on the Basis of Social Partnership - Kulbarshyn M. Meterbayeva, Alima B. Yelkeyeva, Baktygul B. Atabekova, Botagul A. Turgunbaeva, Zeinep Zh. Osmanova,; Besbayev, Madi A. (Opción, 2019)
The article aims to describe the didactic conditions for the development of competitiveness of future teachers based on social partnership in the traditional structure higher school-secondary school via the structural model of higher school-secondary school social partnership. As a result, the higher school – secondary school social partnership has an enormous potential; to disclose the content of each of the above parameters with reference to the conditions for shaping a competitive personality. In conclusion, a high level of competitiveness will be a guarantee of protection of rights and interests of the trained specialists.